Inhibition of Tick-Borne Encephalitis Virus Replication with Eprosartan and Ribavirin In Vitro and In Vivo - G. N. Leonova; O. S. Maistrovskaya; V. A. Lubova (Антибиотики и Химиотерапия)
Active search for new antiviral substances is currently underway. The purpose of this work is to identify the inhibitory activity of eprosartan medication in comparison with ribavirin in vitro and in vivo in relation to tick-borne encephalitis virus. The value of the half the maximum cytotoxic concentration (CC50) for eprosartan (8.8±1.2 mg/ml) and ribavirin (1.074±0.16 mg/ml) was established. To obtain a medium effective virus-inhibiting concentration (IC50) of the medications, EIA data were used. Using nonlinear regression analysis of the percentage of antigen positive samples, IC50 values of the studied substances were obtained, which for eprosartan was 0.64±0.23 mg/ml in the treatment regimen. The selective index (SI) or chemotherapeutic index (CTI) was 13.7. The IC50 of ribavirin was 0.0067±0.0015 mg/ml, SI or CTI was 160. The suppression of viral reproduction 2.0 log TCID50 occurred in PEK cell culture under the influence of eprosartan at concentrations of 1.2–3.0 mg/ml (treatment regimen), under the influence of ribavirin — 0.2 mg/ml (prophylactic regimen) and 0.2–0.0125 mg/ml (treatment regimen). Samples with eprosartan (1.5 and 0.6 mg/ml) showed an increase in survival of mice by 50% and 20% compared with the virus control group in the in vivo model and, accordingly, an increase in average life expectancy of 5.2 and 2.1 days. Samples with ribavirin (0.05 and 0.025 mg/ml) increased the survival of mice by 60% and 40% and, accordingly, increased the life expectancy by 7.3 and 4.8 days. The data obtained allow recommending eprosartan as an active agent against tick-borne encephalitis virus along with ribavirin.